Aboriginal/Anglo Relations as Portrayed in the Folklore of Micmac ‘Witching’ in Newfoundland - Rieti, Barbara (Ethnologies, 1995)
This article examines the social implications of the tradition found in certain parts of Newfoundland that an offended “Indian” can put a “wish” or “spell” on the offender. Narratives typically involve itinerant native basketsellers from Nova Scotia, but have been recorded in connection with Micmac residents of the south coast as well; there is also a group of non-narrative reports about alleged Micmac methods of getting magic power. A full analysis of this material must set it in relation to the larger body of Newfoundland witch lore, but, as a subset with distinctive features, the idea of “Indian curses” poses many questions about native/European interaction. Did it foster fair (if guarded) relations, or hostility - or both ? Did it have a basis in Micmac culture, and did the Micmacs use it, or is it purely a folklore of “otherness.”